La comprensión lectora para potenciar el pensamiento creativo de los estudiantes de octavo año de Educación General Básica de la Unidad Educativa “Dr. Juan Benigno Moncayo, comunidad San José de Arrayán, parroquia Guasuntos, cantón Alausí, provincia de Chimborazo, del año lectivo 2015-2016. - Minchala Yube, Maria Alexandra (2017)
It is important to carry out this research, because it is proposed to determine the influence of reading comprehension in the empowerment of creative thinking of eighth-year students of general basic education in the Educational Unit “Dr. Juan Benigno Moncayo”, San José de Arrayán community, Guasuntos parish, Alausí canton, Chimborazo province, and academic year 2015-2016. About the methodology the type of research used was descriptive. The following is a description of the population of 14 boys and girls of the eighth year of Basic Education in the Educational Unit mentioned above. Among the technique for collecting data from the study group, we worked with the research instrument, the Survey, this instrument helped us to compile the information required for tabulation and analysis, the instrument was the questionnaire, in the elaboration closed questions were established in which the participant has several options of which will mark the answer that in his opinion is the correct one. In conclusion about this work regarding the characteristics of reading comprehension in eighth grade students, it is evident that there is a low level of reading comprehension, it is also evident that children do not perform a clear and expressive oral reading, which makes it difficult to pronounce clearly and with the application of the comprehensible reading process, the children’s ability in creative thinking is developed, defining students to develop the capacity to understand and elaborate the meaning of the relevant ideas of texts Writing, assimilating, analyzing and interpreting the message that contains the text.